Attenuation of Yersinia pestis fyuA Mutants Caused by Iron Uptake Inhibition and Decreased Survivability in Macrophages - Chen, Yulu; Song, Kai; Chen, Xin; Li, Ye; Lv, Ruichen; Zhang, Qingwen; Cui, Yujun; Bi, Yujing; Han, Yanping; Tan, Yafang; Du, Zongmin; Yang, Ruifu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Yersinia pestis is the etiological agent of plague, a deadly infectious disease that has caused millions of deaths throughout history. Obtaining iron from the host is very important for bacterial pathogenicity. Y. pestis possesses many iron uptake systems. Yersiniabactin (Ybt) plays a major role in iron uptake in vivo and in vitro, and in virulence toward mice as well. FyuA, a β-barrel TonB-dependent outer membrane protein, serves as the receptor for Ybt. In this study, we examined the role of the fyuA gene in Y. pestis virulence using different challenging ways and explored the underlying mechanisms. The BALB/c mouse infection assay showed that the virulence of the mutant strains (ΔfyuA and ΔfyuAGCAdel) was lower when compared with that of the wild-type (WT) strain 201. Furthermore, the attenuation of virulence of the mutant strains via subcutaneous and intraperitoneal challenges was far greater than that via intravenous injection. Iron supplementation restored lethality during subcutaneous challenge with the two mutants. Thus, we speculated that the attenuated virulence of the mutant strains toward the mice may be caused by dysfunctional iron uptake. Moreover, ΔfyuA and ΔfyuAGCAdel strains exhibited lower survival rates in murine RAW264.7 macrophages, which might be another reason for the attenuation. We further explored the transcriptomic differences between the WT and mutant strains at different temperatures and found that the expressions of genes related to Ybt synthesis and its regulation were significantly downregulated in the mutant strains. This finding indicates that fyuA might exert a regulatory effect on Ybt. Additionally, the expressions of the components of the type III secretion system were unexpectedly upregulated in the mutants, which is inconsistent with the conventional view that the upregulation of the virulence genes enhances the virulence of the pathogens.